2018
DOI: 10.17219/dmp/91774
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported oral status and habits related to oral care in adult Poles: A questionnaire study

Abstract: Background. Bacterial plaque control plays a key role in the prevention of caries and periodontal diseases. Hygiene negligence in this respect may influence the state of gingiva, and -in the long term -the number of lost teeth. The recommended method of mechanical control of dental plaque is tooth brushing twice a day.Objectives. The aim of the study was to assess the frequency of tooth brushing, the use of various oral hygiene accessories, the number of preserved teeth, and the occurrence of gingival bleeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
2
12
0
1
Order By: Relevance
“…Almas et al revealed that female university students had better oral hygiene practices compared to male students in Saudi Arabia [26]. Even in adults, significant gender difference for the frequency of daily brushing has been reported [27]. Thus, the significant gender difference in oral hygiene behavior observed in this study might point to a common problem worldwide regardless of age.…”
Section: Discussionmentioning
confidence: 49%
“…Almas et al revealed that female university students had better oral hygiene practices compared to male students in Saudi Arabia [26]. Even in adults, significant gender difference for the frequency of daily brushing has been reported [27]. Thus, the significant gender difference in oral hygiene behavior observed in this study might point to a common problem worldwide regardless of age.…”
Section: Discussionmentioning
confidence: 49%
“…The association between dental flossing and proximal caries as seen in Table 3 was found to be strong in men, early middle‐aged adults and frequent snackers. Overall, it is a common problem worldwide for males to have poor oral health behaviours related to lifestyle, knowledge and attitude than females, regardless of age 18,19 . Males are less likely to brush their teeth daily and use ICDs than females and have a higher risk of proximal caries.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, it is a common problem worldwide for males to have poor oral health behaviours related to lifestyle, knowledge and attitude than females, regardless of age. 18,19 Males are less likely to brush their teeth daily and use ICDs than females and have a higher risk of proximal caries. As the use rate of ICDs was highest among participants in their 30s and 40s, it indicates that individuals in this age group are more interested in maintaining oral health than those in other age groups.…”
Section: Discussionmentioning
confidence: 99%
“…A survey on oral hygiene in the entire Polish population was conducted by Górska and Górski in 2018 (survey in 10 cities). The use of dental floss was reported by 57% of the respondents, interdental brushes by 12%, an irrigator by 8%, and mouthwash by 67% [ 36 ]. These results are similar to ours, particularly in terms of the use of an irrigator and mouthwashes.…”
Section: Discussionmentioning
confidence: 99%